A comparative examination of the role of need in the relationship between dental service use and socio-economic status across respondents with distinct needs using data from the Scottish Health Survey - Majed Almutairi; Gerry McKenna; Ciaran O'Neill (BMC, 2023)
Abstract Background Disparities in oral health and distinct patterns in service use related to socio-economic status have been shown to exist in the United Kingdom. A number of studies have used the Andersen behavioural model to better understand the factors that influence utilization and thereby inform policies aimed at improving service uptake. As the nature of need may differ across distinct types of patients, however, so too may the distribution of enabling and pre-disposing factors and observed relationships between need, other factors and service use. In this study we compare samples with distinct self-assessed needs in terms of their characteristics and patterns of service use to compare application of the Andersen model to dental services among respondents to a population based survey. Materials and methods Data were taken from the Scottish Health Survey, for 2019. Data on service use, oral hygiene habits, perceived treatment need, and socio-demographic characteristics were extracted. Data were analysed using descriptive statistics, t-tests and ordered logistic regression analyses. Results Two thousand one hundred forty-eight usable responses were obtained from the survey, 74.95% of the sample had visited the dentist less than a year ago, 11.82% between 1 year and up to 2 years ago, 7.12% between 2 and 5 years ago and 6.10% more than 5 years. Descriptive statistics, t-tests and ordered logistic regression analyses revealed distinct patterns of service use when the sample was partitioned based on perceived treatment need. Specifically those with self-assessed treatment need were older, more likely to smoke, be male and be less likely to have a degree than those who did not. While service use was positively related to age (predisposing) among those who did not have self-assessed treatment need, it was negatively related for those with perceived treatment need. Distinct patterns were also evident with respect to sugar exposure (need) and ease with which time off work could be organised (enabling). Discussion The study shows common and distinct patterns of service use related to enabling and predisposing factors across groups differentiated by self-perceived treatment need. If inequalities in health and healthcare use are to be addressed, it is important to understand their origins. Conflation of distinct types of need that may correlate with predisposing and enabling factors complicates this. Conclusion In applying the Andersen model, it is important to take account of potential differences in the types of need expressed where possible to understand the role of other variables in service use.